A Longitudinal Follow-up Study of Depression, Disability, and Body Concept in Torticollis - M. Jahanshahi; C. D. Marsden (Behavioural Neurology)
Changes in depression, disability, body concept, and severity of head deviation were examined in a sample of 67 patients with idiopathic torticollis, who were reassessed 2 years after taking part in an initial study (before the use of botulinum toxin injections). Over the follow-up period, torticollis was unchanged in 41·8%, had improved in 26·9% and deteriorated in 31·3% of cases. The overall levels of depression, disability, and body concept across the two occasions did not change. Changes in the clinical severity of torticollis over the follow-up period had a significant effect on psychological adjustment. Those whose torticollis improved were less depressed and disabled and a had a more positive body concept compared to the patients whose torticollis had worsened. Measures of illness severity had stronger associations with measures of psychological adjustment at follow-up than at the time of initial study. Longer duration of torticollis was associated with larger increases in depression and disability during the 2 years of follow-up. The results suggest that the experience of depression, disability, and negative body concept in a proportion of torticollis sufferers is a reaction to the neurological illness. A minority of the patients who remain chronically depressed are primary candidates for therapeutic intervention aiming at improving their adjustment to the illness.